Virtual, Augmented, and Mixed Reality in STEM Education in Asia: A Bibliometric Review (2015–2026) - Irwanto, Irwanto (International Journal of Interactive Mobile Technologies (iJIM), 2026)
The use of virtual, augmented, and mixed reality (VAMR) technologies in various domains has increased over recent years. However, reviews of their application in science, technology, engineering, and mathematics (STEM) education, particularly in Asia, remain limited. This study presents a bibliometric review of VAMR research in STEM education in Asia from 2015 to 2026 to map research trends, intellectual structures, and knowledge development in this field. A total of 122 publications were retrieved from the Scopus database. RStudio Bibliometrix and VOSviewer were employed to perform a bibliometric analysis. The findings indicate a steady growth of VAMR research in STEM education among Asian countries over the past decade. Taiwan, China, and Turkey emerged as the most influential countries in terms of citation output. Nanyang Technological University and Universiti Kebangsaan Malaysia were identified as the most productive institutions with 7 publications each. Electronics (Switzerland) was the most influential journal in the field with 266 citations. The most influential article, authored by AlGerafi et al., received 237 citations. Keyword co-occurrence analysis highlighted “augmented reality,” “STEM education,” “STEM,” “virtual reality,” and “systematic review” as dominant themes, reflecting the central focus of current research. This study offers a comprehensive overview of VAMR research in the context of STEM education in Asia and provides a basis for identifying emerging trends and future research directions.